The perception of Students about Teaching Practice in the Foundation phase in South African Schools: The perception of Students about Teaching Practice in the Foundation phase in South African Schools - Nana Yaw Brenya Agyeman (EDUCATIO : Journal of Education, 2025)
Teaching practice is a crucial program that provides aspiring student teachers with practical teaching experience to prepare them for the challenges of teaching in school settings. Teaching practice in the foundation phase is fundamental for the education and development of student teachers. Teaching practice enables them to apply their theoretical knowledge in real teaching scenarios. A recent study examined student teachers' perspectives during their practice in the foundation phases, revealing a range of responses. The study explored student teachers' perceptions of teaching practices using a qualitative research method with a case study design. Six student teachers were purposively selected and interviewed using semi-structured interviews. The findings highlighted the importance of dedicating enough time to teaching practice for professional development. Also, they shed light on the challenges teachers face, such as handling large classrooms and balancing university coursework with teaching practice. Furthermore, the findings underscored the need for improved classroom management and support systems. Schools must address student teachers' challenges during teaching practice while providing adequate support systems to help them maximise their experiences in teaching in the foundation phase. The study recommends that schools and teacher training institutions offer support and resources to help student teachers enhance their professional skills.